New Perspectives for Fisetin - Grynkiewicz, Grzegorz; Demchuk, Oleg M. (Frontiers in Chemistry, 2019)
Fisetin is a flavonol that shares distinct antioxidant properties with a plethora of other plant polyphenols. Additionally, it exhibits a specific biological activity of considerable interest as regards the protection of functional macromolecules against stress which results in the sustenance of normal cells cytoprotection. Moreover, it shows potential as an anti-inflammatory, chemopreventive, chemotherapeutic and recently also senotherapeutic agent. In view of its prospective applications in healthcare and likely demand for fisetin , methods for its preparation and their suitability for pharmaceutical use are discussed herein.